Ecthyma gangrenosum as the presenting clinical feature of autoimmune lymphoproliferative syndrome - Aniruddha Ghosh; Rashmita Das; Partha Pratim Halder; Sandipan Dhar (Wolters Kluwer Medknow Publications, 2018)
Ecthyma gangrenosum (EG) is a severe invasive cutaneous infection caused classically by Pseudomonas aeruginosa typically affecting immunocompromised patients especially those with neutropenia. We report the case of a 2-year-old boy with autoimmune lymphoproliferative syndrome presenting with solitary EG on the forehead. Blood culture, as well as culture from the lesion both, showed growth of P. aeruginosa. Pseudomonal sepsis responded well to piperacillin-tazobactam and amikacin therapy. Prompt diagnosis of the lesion is crucial as failure to start timely appropriate therapy may lead to fatal outcome.